ANALISIS PENGARUH KETIDAKPUASAN KONSUMEN, IKLAN PESAING DAN PERILAKU MENCARI VARIASI TERHADAP PERILAKU PERPINDAHAN MEREK PADA KONSUMEN SHAMPO SUNSILK - Ishadi, Ishadi; Djastuti, Indi (Diponegoro Journal of Management, 2012)
This study is grounded by the decreasing of Sunsilkâ€™s market share in 3 (three) years a row which indicates the occurrence phenomenon of consumer switching from Sunsilk to other shampoo. This phenomenon is usually called brand switching. Therefore, the problem in this study is â€œwhat are the factors that influence consumers switching from shampoo to another shampoo brandâ€. This study examined three independent variables; there are consumer dissatisfaction, competitorâ€™s advertising and variety seeking behavior toward brand switching behavior. The purpose of this study is to find the influence of the independent variables toward brand switching behavior. This study uses a questionnaire method with purposive sampling technique to 100 people who had used Sunsilk before and have switched to another shampoo brand. Then, the writer uses the qualitative and quantitative analysis to analyze the data. The quantitative analysis includes the test of validity, reliability, classic assumption, double regression analysis, test hypotheses and test the feasibility of the model through ANOVAs test and value of adjusted R square. The results of this study indicate that the independent variables used in this study, that consumer dissatisfaction, competitorâ€™s advertising and variety-seeking behavior is feasible to test the dependent variable through the ANOVAs test. The t test results showed that all independent variables are tested has a positive and significant effect on the brand switching behavior. The Adjusted R Square is 0,267 which indicates that 26,7% variation of brand switching behavior can be explained by the two independent variables and the remaining 73,3% is explained by other factors beyond this study.